In vivo activity in a catalytic antibody-prodrug system: Antibody catalyzed etoposide prodrug activation for selective chemotherapy - Shabat, Doron (The National Academy of Sciences, 2001)
Effective chemotherapy remains a key issue for successful cancer treatment in general and neuroblastoma in particular. Here we report a chemotherapeutic strategy based on catalytic antibody-mediated prodrug activation. To study this approach in an animal model of neuroblastoma, we have synthesized prodrugs of etoposide, a drug widely used to treat this cancer in humans. The prodrug incorporates a trigger portion designed to be released by sequential retro-aldol/retro-Michael reactions catalyzed by aldolase antibody 38C2. This unique prodrug was greater than 10(2)-fold less toxic than etoposide itself in in vitro assays against the NXS2 neuroblastoma cell line. Drug activity was restored after activation by antibody 38C2. Proof of principle for local antibody-catalyzed prodrug activation in vivo was established in a syngeneic model of murine neuroblastoma. Mice with established 100-mm(3) s.c. tumors who received one intratumoral injection of antibody 38C2 followed by systemic i.p. injections with the etoposide prodrug showed a 75% reduction in s.c. tumor growth. In contrast, injection of either antibody or prodrug alone had no antitumor effect. Systemic injections of etoposide at the maximum tolerated dose were significantly less effective than the intratumoral antibody 38C2 and systemic etoposide prodrug combination. Significantly, mice treated with the prodrug at 30-fold the maximum tolerated dose of etoposide showed no signs of prodrug toxicity, indicating that the prodrug is not activated by endogenous enzymes. These results suggest that this strategy may provide a new and potentially nonimmunogenic approach for targeted cancer chemotherapy.